Tinjauan Molekuler dan Epidemiologi Mutasi pada Virus SARS-CoV-2 - Hartono Hartono; Yenni Yusuf (bionature, 2021)
Abstract. The SARS-CoV-2 virus which is the cause of the COVID-19 pandemic since the end of 2019 has undergone many mutations that gave rise to several variants of concern (VOC) with higher transmission, virulence, and ability to evade the immune system than the initial variant (wild-type). Until now, there are four variants included in the VOC of the virus, namely alpha, beta, gamma and delta variants. The increased transmission and virulence of these VOCs were associated with mutational changes in the spike protein, which is the structure of the virus that plays a role in binding to host cells. In this article, we conduct a literature review on VOCs from the SARS-CoV-2 virus related to mutations that occur and their impact on the viral binding process. To gain an understanding of the impact of mutations in these variants, we also reviewed the structure of the spike protein and the process of viral entry into host cells. Keywords: viral mutation, variants of concern (VOC), COVID-19, SARS-CoV-2.